Free vibration properties of beetle elytron plate: Composite material, stacked structure and boundary conditions - Song, Yiheng; Hao, Ning; Ruan, Sihan; He, Chaochao; Quanjin, Ma (Elsevier B.V., 2023)
Beetle elytron plate (BEP), which is derived from the bionics of Trypoxylus dichotomus's elytra, is a typical lightweight and high-strength structure with superior and comprehensive mechanical properties. To promote the engineering application of BEPs, this paper explores the vibration characteristics of foam-filled fiber composite BEPs. Through the finite element method (FEM), structural parameters such as the length-to-width ratio, core height-to-thickness ratio, skin thickness and foam density influence the natural frequency and mode. Furthermore, the influence pattern of parameters (such as boundary conditions and the number of stacked layers) toward the first two orders of natural frequencies and modes of the BEP were investigated under controlled total height and controlled single layer height. The results indicate that 1) the ranking of structural parameters on the 1st order frequency from a strong to weak sequence is as follows: length-to-width ratio, core height-to-thickness ratio, foam density and skin thickness; for the 2nd order natural frequency: length-to-width ratio, skin thickness, foam density and core height-to-thickness ratio. 2) Generally, an increase in the length-to-width ratio will reduce the frequency of the BEP, and increases in the core height-to-thickness ratio and skin thickness will raise its frequency. Additionally, foam filling plays a decisive role in local deformation. 3) When the total height of the sandwich plate is controlled, the improvement of the boundary conditions can effectively boost its 2nd-order frequency (approximately 200%), but the 1st-order frequency can be significantly increased (approximately 140%) only when all four sides are improved. 4) In the case of controlling the height of the single layer of the sandwich plate, its frequency gradually increases with the increase in the number of stacked layers. However, when the constraints are weak or there are few stacked layers, increasing the number of stacked layers can effectively boost the vibration frequency. This paper provides references and suggestions for the design and application of sandwich structures, enriching the research on the mechanical properties of BEPs and establishing groundwork for promoting BEPs in engineering practices.